True phosphorus absorption from dicalcium phosphate, monoammonium phosphate, triple superphosphate, and urea phosphate in bovines - Filho, José Cleto da Silva; Lopes, Henrique Otávio da Silva; Pereira, Eurípedes Alves; Meirelles, Cyro Ferreira; Vitti, Dorinha Miriam Silber Schmidt; Abdalla, Adibe Luiz (Pesquisa Agropecuaria Brasileira, 1992)
With the aim to study the utilization of alternative sources of phosphorus by ruminants, a metabolism trial was carried out where the true absorption of the phosphorus from dicalcium phosphate (DICAL), monoammonium phosphate (MAP), supertriple phosphate (STP) and urea-phosphate (UP) was determined by using the radioisotope dilution technique. Twenty-four male steers, with 250 kg live weight and about 20 months old, were allocated in four groups of six animals each. The animals were housed in individual pens and received a basal diet containing chopped hay of Brachiaria decumbens, corn and soybean meal, urea and a mineral mixture. The phosphate sources studied were added to supply 10 g of phosphorus per animal daily. The animals were injected intravenously and individually with 37 MBq of P-32 (Na2HPO4) into the jugular vein. Blood and feces were collected and sampled at 24 hour intervals, for 10 days. Based on the specific activities calculated of plasma and feces, the fecal endogenous loss and the true phosphorus absorption were determined. The true phosphorus absorption values were 68,05 ± 6,37; 65,13 ± 8,44; 62,25 ± 6,10 and 58,38 ± 5,35% respectively for DICAL, STP, UP and MAP, without any significance among the treatments (P "